PENGARUH INFLASI DAN SUKU BUNGA TERHADAP KINERJA REKSADANA TAHUN 2015-2023 : PENGARUH INFLASI DAN SUKU BUNGA TERHADAP KINERJA REKSADANA TAHUN 2015-2023 - Mohammad Ilham; Maulina Sari , Sherly Putri; Doras Talo, Rio Firas; Perdini Fisabilillah, Ladi Wajuba; Dewi, Dita Dismalasari (Jurnal Ekonomika : INDEPENDEN, 2024)
The capital market investment in Indonesia is currently growing rapidly and offering many options. One example of an investment is mutual funds. Mutual funds are investment instruments that pool funds from many investors to be managed by investment managers. Investment performance can be measured through the Net Asset Value (NAV) of mutual funds. The purpose of this study is to determine the influence of inflation and interest rates on the performance of mutual funds. The method used is quantitative research employing multiple regression analysis. The results of this study indicate that inflation and interest rates simultaneously have a significant effect on the performance of mutual funds. Partially, both inflation and interest rates individually have a significant negative impact on the performance of mutual funds. Keywords: Mutual Funds, Inflation, Interest Rates